Eksposisi Gambar Allah Menurut Penciptaan Manusia Berdasarkan Kejadian 1:26-28 (International Forum of Researchers and Lecturers, 2023)
The purpose of human creation based on the context of Genesis 1:26-28 is that humans were created to relate to other creatures and also to fellow human beings where God wants humans to be fruitful and multiply to fill the earth. Allah created man to fulfill His plan and all His creations belong to Him. The image of God in man reflects the personality of God before man fell into sin. And humans who were created in God's image have the responsibility to subdue all of His creation as a responsibility for God's sovereignty as His representative on earth.